# Question #5db08

##### 1 Answer

Jul 22, 2016

#### Explanation:

Your starting equation looks like this

#xz + y + 1 = z#

Your goal here is to solve this equation for

The first thing to do here is add

#xz + color(red)(cancel(color(black)(y + 1))) - color(red)(cancel(color(black)((y + 1)))) = z - (y+1)#

This is equivalent to

#xz = z - (y + 1)#

Now all you have to do is divide both sides of the equation by

#(x * color(red)(cancel(color(black)(z))))/color(red)(cancel(color(black)(z))) = (z-(y+1))/z#

Your answer will be

#x = (z - (y+1))/z = z/z - (y+1)/z = 1 - (y+1)/z#

Notice that you need to have